Cardiovascular and metabolic status in patients with primary hyperparathyroidism: a single-center experience - Dobreva, Ekaterina A.; Gorbacheva, Anna M.; Bibik, Ekaterina E.; Eremkina, Anna K.; Elfimova, Alina R.; Salimkhanov, Rustam Kh.; Kovaleva, Elena V.; Maganeva, Irina S.; Mokrysheva, Natalia G. (Frontiers in Endocrinology, 2023)
Cardiovascular diseases (CVD) and metabolic disorders (MD) have retained leading positions in the structure of morbidity and mortality for many years. Primary hyperparathyroidism (PHPT) is also associated with a greater incidence of CVD and MD. The aim of the present study was to describe the prevalence and structure of CVD and MD in hospitalized patients with PHPT and to search for possible associations between these pathologies. 838 patients with a verified PHPT were included in the study. The studied cohort was divided into 2 groups according to their age at the time of admission: patients aged 18 to 49 years (group A, n = 150); patients aged 50 years and older (group B, n = 688). There were no significant differences between two groups in parameters of calcium-phosphorus metabolism. Obesity was diagnosed in 24.2% of patients in group A and in 35.9% in group B. Type 2 diabetes mellitus was more common in older patients (14.4% in group B vs. 2.6% in group A). Arterial hypertension, ischemic heart disease, chronic heart failure and brachiocephalic arteries atherosclerosis were more frequent in older patients, occurring in 79.1%, 10.8%, 8.4%, and 84% of cases respectively. The cutoff points that increased the risk of CVD detection turned out to be age above 56 years, eGFR below 92 ml/min/1.73m2, BMI above 28.3 kg/m2. Thus, the present study demonstrated a high incidence of some CVD, as well as disorders of lipid, carbohydrate and purine metabolism in patients with PHPT.